Caracterización química de la sangre de drago (Croton lechleri) para su potencial uso en Medicina Veterinaria - Guaillas Zhondo, Benito Fabián (2025)
Drago’s Blood (Croton lechleri) is a plant resin widely used for its therapeutic properties in traditional medicine, particularly as a wound healer, antimicrobial, and anti-inflammatory agent. This study aimed to chemically characterize its compounds to assess their potential use in veterinary medicine through thin-layer and column chromatography. Samples were collected in the parish of Nuevo Paraíso, Nangaritza Canton, Zamora Chinchipe Province, and analyzed using thin-layer chromatography (TLC) and column chromatography. Seven bioactive compounds were identified: proanthocyanidins (polymeric flavonoids) with a retention factor (Rf) of 0.2 to 0.4, taspine (alkaloid) with an Rf of 0.5 to 0.6, catechins (monomeric flavonoids) with an Rf of 0.3 to 0.5, gallic acid (phenolic acid) with an Rf of 0.4 to 0.6, terpenes (mono- and sesquiterpenes) with an Rf of 0.7 to 0.8, β-sitosterol (sterol) with an Rf of 0.6 to 0.7, and lignans (dimethylcedrusin) with an Rf of 0.5 to 0.7. Column chromatography enabled the separation of these compounds into seven fractions, confirming their presence and therapeutic relevance. The identified bioactive properties include wound-healing, anti-inflammatory, antimicrobial, antioxidant, and antiviral effects, with taspine, lignans, proanthocyanidins, β-sitosterol, catechins, and gallic acid being particularly noteworthy. These findings support the potential of Drago’s blood in veterinary medicine, solidifying it as a valuable natural resource for developing new therapeutic alternatives.